Training in Honey Bee Veterinary Medicine in Italy: An Observational Study and Practical Proposals to Face Professional Challenges - Carlo D’Ascenzi; Karen Power; Paola Maiolino; Michele Mortarino (Animals, 2023)
Honey bees, like other livestock, may be affected by infectious, parasitic, and abiotic diseases that need proper sanitary monitoring and control. Currently, there are limited opportunities for undergraduate students to receive education in Honey Bee Veterinary Medicine (HBVM) as part of their regular degree program, despite the professional requirements for veterinarians to carry out the increasing tasks related to honey bee health and production. Additionally, postgraduate training and specialization in HBVM is also underdeveloped. This study was an observational survey that evaluated the educational opportunities available in HBVM for current and future veterinarians in Italy. The survey analyzed both undergraduate and postgraduate programs, including Undergraduate Degree Programs in Veterinary Medicine (UDPVM), “Scuole di Specializzazione”, Masters, and other postgraduate courses. The results indicate that the current training available for veterinarians in the field of apiculture, both before and after graduation, is also insufficient in Italy, as already reported in other EU- and extra-EU countries. Finally, a roadmap for veterinary training in HBVM is developed here describing objectives and teachings aimed at fulfilling the needs of the profession in the field of beekeeping, considering the existing rules and regulations governing public health and possible evolution of this legal framework in the future.